Послушный зайчонок: стихи / Гайда Лагздынь - Лагздынь Г. (Дет. лит., 1988)
Экземпляры: до (ретроконверсия) / Инвентарный номер: 24943 / Цена: 1.50 / Сис.шифр: Д / Авт.знак: Л 14 / ГРНТИ: 17.82 / ББК: 84(2=411.2)